Epithelioid hemangioendothelioma with multiple organ involvement - ÇELİKEL, ÇİĞDEM; YUMUK, PERRAN FULDEN (WILEY, 2007)
Epithelioid hemangioendothelioma is a rare vascular neoplasm of uncertain malignant potential. Various reports document metastatic or concurrent epithelioid hemangioendothelioma in several sites, most commonly with combined lung and liver involvement. The concurrent involvement of multiple sites at presentation may cause diagnostic problems because epithelioid hemangioendothelioma can mimic other neoplastic processes. Although it is a chemoresistant disease, chemotherapy is usually advised for patients with metastatic or concurrent involvement. Here we document the presentation, treatment, and outcome of two cases with concurrent involvement of the lung and liver.
Keywords: epithelioid; hemangioendothelioma; liver; lung; pleura; LIVER; LUNG; TRANSPLANTATION; PLEURA; TUMOR